Optimum design of dynamic modal control algorithm using non-linear structural mathematical modeling - Corbi, Ileana; Corbi, Ottavia; Li, Haitao (Soil dynamics and earthquake engineering (1984), 2018)
The paper falls within the framework of dynamic control of existing structures exhibiting non-linear behaviour. On the basis of some previous research developed by the authors, it specifically focuses on the analytical setup and development of a control algorithm for mitigating in an improved way the response of non-linear spatial structures, made of masonry. The presented setup does not involve the gross simplifications of the structural model behaviour that are usually adopted in these cases; on the contrary it proposes a more appropriate full mathematical formulation, which is, nevertheless, made still manageable for numerical purposes and significantly more reliable than alternative approaches. •An original dynamic control algorithm is optimally designed accounting for non-linear structural response.•The full analytical treatment of non-linear structural behaviour is performed.•An energetic approach is setup in the modal space for optimally tuning the control action.•Numerical implementation shows the significant dynamic mitigation achieved through the proposed approach.